2018
DOI: 10.1111/hae.13508
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand disease: Clinical conundrums

Abstract: In this short review, current clinical conundrums on von Willebrand disease (VWD) will be addressed. Despite more knowledge on the pathophysiology of VWD, improvement of diagnostic strategies and advances in clinical care for patients with VWD still several problems and dilemmas remain. In this review, the latest findings regarding the pathology, including controversial borders for definition of the disease, diagnostic dilemma when von Willebrand factor (VWF) levels evolve with age, laboratory issues rendering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
0
12
0
2
Order By: Relevance
“…Excessive mucocutaneous bleeding is the primary symptom but this ranges from mild to severe; patients completely lacking VWF experience moderate to severe bleeding symptoms including epistaxis, menorrhagia, postoperative bleeding and haemarthrosis that also may be present in cases with partial VWF function (e.g. type 2N VWD) 1‐6 . Based on ISTH recommendations, 1,2 the diagnosis of VWD involves an algorithm that includes biochemical screening tests (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive mucocutaneous bleeding is the primary symptom but this ranges from mild to severe; patients completely lacking VWF experience moderate to severe bleeding symptoms including epistaxis, menorrhagia, postoperative bleeding and haemarthrosis that also may be present in cases with partial VWF function (e.g. type 2N VWD) 1‐6 . Based on ISTH recommendations, 1,2 the diagnosis of VWD involves an algorithm that includes biochemical screening tests (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…10 These advances have led to an increasingly complicated decision-making process, reflected by the complex impact that hemostatic imbalance can have on the complement system, immunity, and inflammation and, therefore, the management of hemostatic disorders. 11,12 This situation is compounded, in some instances, where access to even basic laboratory testing and medications is limited, 13 as are opportunities to access the latest scientific knowledge, tests, devices, or medications, compromising provision of optimal clinical care. 14 Given this rapidly evolving context, educational activities are needed to ensure optimal knowledge dissemination to T&H professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding disorder associated with VWF is known as von Willebrand disease (VWD) and has been the leading influence in identification, characterization, and determination of function for VWF molecule. VWD, which has been the subject of many excellent reviews periodically, can be broadly classified into categories that represent qualitative (type II) or quantitative (type I and III) deficiencies of VWF . In either case, VWF deficiency is the culprit leading to prolonged bleeding phenotype, some forms of which are reminiscent of hemophilia that arise as a result of coagulation factor VIII deficiency .…”
Section: Introductionmentioning
confidence: 99%
“…The two major functions of VWF have been long established as: (a) mediator of platelet adhesion and aggregate formation at the site of vascular injury, leading to formation of platelet plugs to seal the damaged vessel wall and (b) functioning as carrier for factor VIII, thus prolonging its half‐life in circulation . Although severe deficiencies of VWF clearly correlated to significant bleeding disorders, milder deficiencies were also identified that manifested only as a result of hemostatic challenges, such as surgeries, or menorrhagia . Wide variation in VWF levels among healthy population hinders diagnosis of mild VWD, but also made it difficult to appreciate potential pathological consequences of high levels of VWF .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation